Perbandingan Kinerja Reksa Dana Konvensional dengan Indeks Konvensional (LQ45) - Cahyaningsih Cahyaningsih (Jurnal Akuntansi dan Bisnis, 2010)
The objective of this study is to evaluate whether conventional mutual fund performance is difference from conventional index (LQ45) performance during the bull market of 2004 to 2006. Prior studies have shown mixed results probably due to lack of comprehensiveness in evaluating the portfolio. I measure mutual fund performance comprehensively using Jensen Index, Sharpe Index, Treynor Index, MM Index, and TT Index. The results show that during the bull market of 2004 to 2006, the conventional mutual funds outperform the conventional indexs (LQ45). This results might suggest that portofolio managers of the conventional mutual fund have superior skills in security selection and market timing ability than those of the conventional indexs (LQ45).